Premalignant Conditions of Bone. (13th October 2022) - Eckhoff, Michael D.; Wells, Matthew E.; Padilla, Osvaldo; Polfer, Elizabeth M.; Castagno, Christopher J.; Thabet, Ahmed M.; Elzamly, Shaimaa; Wilson, Harry L.; Rajani, Rajiv
Abstract : Development of malignancy is a multifactorial process, and there are multitude of conditions of bone that may predispose patients to malignancy. Etiologies of malignancy include benign osseous conditions, genetic predisposition, and extrinsic conditions. New-onset pain or growth in a previously stable lesion is that should concern for malignant change and should prompt a diagnostic workup for malignancy.